2009
DOI: 10.1080/15622970902980770
|View full text |Cite
|
Sign up to set email alerts
|

Irreversibility of cardiac autonomic dysfunction in female adolescents diagnosed with anorexia nervosa after short- and long-term weight gain

Abstract: Anorexia nervosa (AN) patients may present with cardiac autonomic system dysfunction. Power spectral analysis of heart rate variability (HRV) is a reliable noninvasive examination for the quantitative assessment of the central sympathovagal interaction that modulates cardiovascular autonomic function. In the present study, HRV parameters were assessed in female adolescent AN inpatients in the malnourished phase at admission, at discharge when achieving weight restoration, and 24-36 months after discharge, when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 50 publications
2
41
1
2
Order By: Relevance
“…The time and frequency domain analysis in seated subjects showed no significant differences between the control and AN group in agreement with some previous studies [26,24,37]. A decreased low frequency power was found in our study but was not significant in contrast to studies reported by [38,2,22].…”
Section: Hrv Measurescontrasting
confidence: 49%
See 1 more Smart Citation
“…The time and frequency domain analysis in seated subjects showed no significant differences between the control and AN group in agreement with some previous studies [26,24,37]. A decreased low frequency power was found in our study but was not significant in contrast to studies reported by [38,2,22].…”
Section: Hrv Measurescontrasting
confidence: 49%
“…However, the studies in AN patients primarily utilized linear methods to evaluate sympathovagal balance. Several of these studies have reported decreased vagal tone whilst others found an increase in parasympathetic activity [21,22,6,[23][24][25]. Other studies report no change or altered sympathovagal balance [26,27].…”
Section: Introductionmentioning
confidence: 95%
“…Although QT prolongation in AN is largely reversible with appropriate nutrition, 4,5,32,33 overt autonomic dysfunction (and possibly impaired repolarization reserve) may persist for several years despite adequate refeeding and relative normalization of the BMI. 48 Indeed, the highest BMI tertile among patients was of comparable body mass to the control group as a whole; however, despite this, the QT/RR slope was still more gradual in the patients. Therefore, BMI alone may not confidently predict arrhythmic risk, and further studies are required to elaborate on risk factors for arrhythmia in AN, possibly QT/RR slope.…”
Section: Discussionmentioning
confidence: 99%
“…São utilizados tambémpara melhor compreensão darelação de certas doenças e a modulação autonômica. Em estudo com mulheres diagnosticadas com Anorexia Nervosa, os autores encontraram uma redução da frequência cardíaca, uma baixa VFC, redução no componente LF e elevação no HF sugerindo uma disfunção cardíaca autonômica na forma de anormalidades no controle vagal cardíaco 12 ; Na epilepsia a redução da VFC, durante o período interictal, é caracterizado por diminuição de HF, rMSSD, pNN50 e aumento da relação LF/ HF, refletindo a redução do tônus vagal cardíaco 19,20 .…”
Section: Aplicabilidade Clínica Da Vfcunclassified